Whereas - Long Soldier, Layli (Graywolf Press, 2017)
This volume confronts the coercive language of the United States government in its responses, treaties, and apologies to Native American peoples and tribes, and reflects that language in its officiousness and duplicity back on its perpetrators. Through an array of short lyrics, prose poems, longer narrative sequences, resolutions, and disclaimers, Layli Long Soldier has created an innovative text to examine histories, landscapes, her own writing, and her predicament inside national affiliations. "I am," she writes, "a citizen of the United States and an enrolled member of the Oglala Sioux Tribe, meaning I am a citizen of the Oglala Lakota Nation -- and in this dual citizenship I must work, I must eat, I must art, I must mother, I must friend, I must listen, I must observe, constantly I must live."